Epidemiological assessment of neglected diseases in children: lymphatic filariasis and soil-transmitted helminthiasis - Ana M. Aguiar-Santos; Zulma Medeiros; Cristine Bonfim; Abraham C. Rocha; Eduardo Brandão; Tereza Miranda; Paula Oliveira; Emanuel S.C. Sarinho (Elsevier, 2013)
Objective: To report the prevalence of lymphatic filariasis and intestinal parasitic infections in school-aged children living in a filariasis endemic area and discuss about the therapeutic regimen adopted in Brazil for the large-scale treatment of filariasis. Methods: A cross-sectional study including 508 students aged 5-18 years old, enrolled in public schools within the city of Olinda, Pernambuco. The presence of intestinal parasites was analyzed using the Hoffman, Pons and Janer method on 3 stool samples. The diagnosis of filarial infection was performed using the rapid immunochromatographic technique (ICT) for the antigen, and the polycarbonate membrane filtration for the presence of microfilariae. Descriptive statistics of the data was performed using EpiInfo version 7. Results: The prevalence of filariasis was 13.8% by ICT and 1.2% by microfilaraemia, while intestinal parasites were detected in 64.2% of cases. Concurrent diagnosis of filariasis and intestinal parasites was 9.4%, while 31.5% of students were parasite-free. Among individuals with intestinal parasites, 55% had one parasite and 45% had more than one parasite. Geohelminths occurred in 72.5% of the parasited individuals. In the group with filarial infection the prevalence of soil-transmitted helminthiasis was 54.5%. Conclusions: The simultaneous diagnosis of filariasis and intestinal parasites as well as the high frequency of geohelminths justify the need to reevaluate the treatment strategy used in the Brazilian filariasis large-scale treatment program. Resumo: Objetivo: Descrever a prevalência de infecção filarial e de parasitoses intestinais em escolares numa área endêmica de filariose e refletir sobre a opção terapêutica utilizada no Brasil no tratamento coletivo para filariose. Métodos: Estudo transversal envolvendo 508 alunos na faixa etária de 5-18 anos cadastrados em escolas públicas do município de Olinda-PE. Realizou-se a investigação da parasitose intestinal em três amostras de fezes, analisadas pelo método de Hoffmann, Pons e Janer. A investigação filarial foi feita com teste antigênico pela técnica de imunocromatográfica rápida (ICT) e pesquisa de microfilárias, utilizando filtração em membrana de policarbonato. Para análise de dados utilizou-se a estatística descritiva através do programa EpiInfo versão 7. Resultados: A prevalência de filariose por ICT foi de 13,8% e por microfilaremia de 1,2%, enquanto a de parasitoses intestinais foi 64,2%. A concomitância do diagnóstico filarial e de parasitoses intestinais foi de 9,4% e, 31,5% eram isentos de ambas as parasitoses. Entre os indivíduos com parasitoses intestinais, 55% eram monoparasitados e 45% poliparasitados. A presença de geohelmintos ocorreu em 72,5% dos parasitados. No grupo com infecção filarial a ocorrência de geohelmintíase foi de 54,5%. Conclusões: O diagnóstico simultâneo de infecção filarial e parasitose intestinal, bem como a elevada frequência de geohelmintos justificam uma reavaliação da estratégia terapêutica do tratamento coletivo no programa de filariose no Brasil. Keywords: Filariasis, Helminthiasis, Neglected diseases, Intestinal parasitic, Prevention and control, Palavras-chave: Filariose linfática, Helmintíase, Doenças negligenciadas, Enteropatias parasitárias, Prevenção e controle